Coarctation of the Aorta in Adolescence: Significance of Detailed Cardiac Examination in Pediatric Hypertension. Issue 12 (10th December 2021) - Asad, Imran; Lee, Michelle Sin; Banihani, Rudaina; Wong, Peter D.; Etoom, Yousef
Abstract: Although coarctation of the aorta (CoAo) is a congenital anomaly, it can pose a diagnostic challenge in those presenting beyond neonatal period, as some patients can remain asymptomatic until complications of hypertension develop later in life. Careful physical examination can play an important role in timely diagnosis and prevention of complications. We present 2 cases of adolescents with undiagnosed CoAo who both presented with nonspecific headaches and hypertension. Both were initially misdiagnosed as essential hypertension until careful detailed physical examination later detected weak/absent femoral pulses and discrepancy in upper and lower limb blood pressures. These findings raised the clinical suspicion of CoAo, which was confirmed on further investigations. Our cases highlight the importance of considering CoAo in the differential diagnosis of hypertension in adolescents. These cases also stress the significance of detailed cardiac examination including 4-limb blood pressure and femoral pulses in a patient presenting to the emergency department with high blood pressure irrespective of the primary complaint.